Stories of Change Case Study Approach Used to Support Nutrition Policy Decisions in Rwanda: Successful Advocacy at Local and District Level - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Stories of Change is a structured case study approach which systematically assesses and analyzes drivers of nutritional change in specific country contexts. These resulting ‘stories’ improve our understanding of what drives impact in reducing undernutrition, and how enabling environments and pro-nutrition policy and implementation processes can be cultivated and sustained. The Story of Change case study approach in Rwanda resulted in a better understanding of the national drivers of change in nutrition and recommendations for future improvements.